Stereotyping at the multicultural workplace. The case of Jewish, Chinese, and American immigrant in multicultural workplaces in Singapore and Malaysia - Wong, Loong Wei (2025)
Antisemitism, the stereotype or prejudice against the Jewish community, has gained significant global attention, particularly in the aftermath of the Israel-Hamas conflict, also known as the Gaza War. According to the Anti-Defamation League, there has been a reported increase of over 300% in antisemitic incidents since the war, primarily in the United States and European countries. Concurrently, discussions around the opposite phenomenon, philosemitism, have also seen a notable rise.